Sediment and nutrient lost by runoff from two watersheds, Digga district in Blue Nile basin, Ethiopia - Wudneh, A.; Erkossa, Teklu; Devi, P. (Academic Journals, 2014)
The study was conducted in two sub watersheds in the Upper Blue Nile Basin in Ethiopia to determine the quantity, quality of sediment lost and its onsite costs in terms of crop yield. Two monitoring stations at the outlets were selected. Discharges were estimated and depth integrated daily runoff samples were collected during the rainy season in 2011. The sediment concentration and nitrogen (N) and phosphorus (P) content was analyzed and related to crop yield using a nutrient response equation for maize (Zea mays). The result shows statistically significant differences in sediment concentration of the two watersheds. Suspended sediment concentration was strongly correlated with the discharge from Chekorsa River (R2 = 0.7) but it was very weak for Dapo. There was higher concentration of nutrients in the sediment than the surface soil in both watersheds. Particularly, sediment enrichment ratio of available P was 2.7 and 9 for Dapo and Chekorsa Rivers, respectively. The estimated yield reduction of maize due to N and P loss was about 950 and 1420, and 1015 and 665 kgha-1 from Dapo and Chekorsa catchments, respectively. Such results are equivalent to an onsite cost to farmers of about 190 and 285 USD ha-1 for Dapo, and 203 and 133 USDha-1 for Chekorsa catchments in that order. This monetary value can alert farmers and decision makers to take soil and water conservation measures.